KECERDASAN LOGIS MATEMATIS TERHADAP DISPOSISI MATEMATIS SISWA - Taza Yuni Vira; Aniswita, Aniswita (Dharmas Education Journal (DE_Journal), 2022)
The research is based on the results of observations and interviews at SMP Negeri 2 Bukik Barisan, it can be seen that students' mathematical disposition abilities are less than optimal, this is thought to be due to the influence of students' logical mathematical intelligence. This research is correlational. This research aims to determine the effect of mathematical logical intelligence on the mathematical disposition of students in class VIII of SMP Negeri 2 Bukik Barisan in the 2021/2022 academic year. The population taken as many as 99 students of class VIII. The research sample was 30 students who were taken randomly. The instrument uses a test to measure mathematical logical intelligence and a questionnaire to measure mathematical disposition. Data were analyzed by simple linear regression. The research results obtained t_count>t_table=2.181>1.071, so that mathematical logical intelligence affects the mathematical disposition of Class VIII students of SMP Negeri 2 Bukik Barisan in the 2021/2022 academic year.